MECHANISMS FOR INCREASING MOTIVATION TO LEARN COMMUNICATIVE SKILLS IN FOREIGN LANGUAGES AMONG MEDICAL STUDENTS IN UZBEKISTAN: PROBLEMS AND SOLUTIONS (The Journal of Interdisciplinary Human Studies, 2026)
This article reviews Uzbekistan-specific challenges, drawing on localstudies (e.g., Fozilova, 2026; Madraximova, 2026) and comparative evidence fromnon-Anglophone contexts. It proposes targeted mechanisms grounded in Dörnyei’sL2 Motivational Self System and Self-Determination Theory: mandatory early-yearEMP integration aligned with clinical subjects and national reforms, peer-assistedlearning (PAL) in mixed local-international groups, blended learning via platformslike Moodle/HEMIS with gamification and role-playing simulations, and institutionalsupport including specialized teacher training and language centers. These strategiesaim to enhance instrumentality (career benefits), strengthen the Ideal L2 Self (visionas a globally competitive doctor), reduce anxiety, and promote sustainable engagementamid Uzbekistan’s drive for international medical education competitiveness.
Keywords: medical education; English for Medical Purposes (EMP); student motivation; English-Medium Instruction (EMI); L2 Motivational Self System; peer-assisted learning; blended learning